Formalisms for Reuse and Systems Integration - Bouabana-Tebibel, Thouraya.; Bouabana-Tebibel, Thouraya.; Rubin, Stuart H.; Rubin, Stuart H. (Advances in Intelligent Systems and Computing,, 2015)
Reuse and integration are defined as synergistic concepts, where reuse addresses how to minimize redundancy in the creation of components; while, integration focuses on component composition. Integration supports reuse and vice versa. These related concepts support the design of software and systems for maximizing performance while minimizing cost. Knowledge, like data, is subject to reuse; and, each can be interpreted as the other. This means that inherent complexity, a measure of the potential utility of a system, is directly proportional to the extent to which it maximizes reuse and integration. Formal methods can provide an appropriate context for the rigorous handling of these synergistic concepts. Furthermore, formal languages allow for non ambiguous model specification; and, formal verification techniques provide support for insuring the validity of reuse and integration mechanisms.   This edited book includes 12 high quality research papers written by experts in formal aspects of reuse and integration to cover the most recent advances in the field. These papers are extended versions of some of the best papers, which were presented at the IEEE International Conference on Information Reuse and Integration and the IEEE International Workshop on Formal Methods Integration - both of which were held in San Francisco in August 2014.